Imam al-Ghazali's Concept of Religious Counseling in Forming Moderate Attitudes - Siregar, Pahri; Nurihsan, Juntika; Yusuf, Syamsu; Budiman, Nandang (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
The increasing polarization of religious attitudes in contemporary society necessitates exploring historical and theological resources that promote moderation and balance. This article delves into Imam al-Ghazali's concept of religious counseling, aiming to understand its principles and methods that can cultivate moderate attitudes among individuals and communities. Employing a qualitative approach with a focus on literature review, this research analyzes Ghazali's seminal works, particularly Ihya' Ulum al-Din and Mizan al-'Amal, to uncover how his teachings contribute to fostering spiritual well-being, ethical behavior, and social harmony. Imam al-Ghazali's emphasis on moderation, ethical conduct, and integrating spiritual and social responsibilities significantly contribute to religious counseling in contemporary contexts. His advocacy for the middle path (wasatiyyah) offers a robust framework that addresses the pressing challenges of extremism and polarization. Ghazali's teachings encourage practitioners of religious counseling to promote balance and harmony within their communities by emphasizing ethical behavior rooted in Islamic virtues. Ghazali underscores the importance of maintaining mutual respect, tolerance, and constructive dialogue across diverse backgrounds by fostering an understanding of the interconnectedness between personal spirituality and communal welfare. This approach enriches individual spiritual well-being and enhances social cohesion by encouraging individuals to fulfill their religious obligations while actively engaging in societal improvement efforts. By mitigating the root causes of extremism through a holistic approach to counseling, Ghazali's teachings provide invaluable guidance for religious counselors seeking to effectively navigate and reduce contemporary social challenges. Polarisasi meningkatnya sikap-sikap keagamaan dalam masyarakat kontemporer menuntut eksplorasi sumber-sumber sejarah dan teologis yang mempromosikan moderasi dan keseimbangan. Artikel ini menggali konsep konseling keagamaan Imam Ghazali, bertujuan untuk memahami prinsip-prinsip dan metodenya yang dapat membudayakan sikap moderat di kalangan individu dan komunitas. Dengan pendekatan kualitatif yang berfokus pada tinjauan literatur, penelitian ini menganalisis karya-karya Ghazali yang mendasar, terutama Ihya' Ulum al-Din dan Mizan al-'Amal, untuk mengungkap bagaimana ajarannya berkontribusi dalam memajukan kesejahteraan spiritual, perilaku etis, dan harmoni sosial. Penekanan Imam Ghazali pada moderasi, perilaku etis, dan integrasi tanggung jawab spiritual dan sosial memberikan kontribusi signifikan dalam konseling keagamaan pada konteks kontemporer. Perhatiannya terhadap wasatiyyah menawarkan kerangka kerja yang kokoh yang menangani tantangan-tantangan mendesak ekstremisme dan polarisasi. Ajaran Ghazali mendorong praktisi konseling keagamaan untuk mempromosikan keseimbangan dan harmoni dalam komunitas mereka dengan menekankan perilaku etis yang berakar pada kebajikan Islam. Dengan memupuk pemahaman tentang keterkaitan antara spiritualitas pribadi dan kesejahteraan komunal, Ghazali menegaskan pentingnya memelihara saling menghargai, toleransi, dan dialog konstruktif lintas latar belakang yang beragam. Pendekatan ini tidak hanya memperkaya kesejahteraan spiritual individu tetapi juga meningkatkan kohesi sosial dengan mendorong individu untuk memenuhi kewajiban keagamaan mereka sambil aktif terlibat dalam upaya perbaikan sosial. Dengan mengurangi akar penyebab ekstremisme melalui pendekatan holistik dalam konseling, ajaran Ghazali memberikan panduan berharga bagi konselor keagamaan yang ingin menavigasi dan mengatasi tantangan sosial kontemporer secara efektif.